Performance Analysis of an OFDM PHY Scheme with Zero Forcing Equalizer Using Software Defined Radio Platform and USRP - Zainudin, Ahmad; Sudarsono, Amang; Astawa, I Gede Puja (Politeknik Elektronika Negeri Surabaya (PENS), 2014)
We present an implementation of Zero Forcing (ZF) equalizer in OFDM scheme using Software Defined Radio platform whereas NI USRP-2920 as the Radio Frequency (RF) front-end. ZF equalizer is employed to achieve reliable system at the receiver. Center frequency used for data transmission is 915 MHz. The reliability transmission and the performance of ZF equalizer are measured in term of different symbol mapping (i.e., M-PSK and M-QAM). The IQ rate determines the bandwidth available, whereas good performance is achieved with IQ rate less than 1 MHz.ZF equalizer achieves good performance when using BPSK, QPSK and 16-QAM modulation techniques. By applying ZF equalizer, bit error on BPSK and QPSK modulations can be reduced from 29,16% and 39,06% into 0%. This advantage of ZF equalizer also is able to press the bit error on 16- QAM and 64-QAM modulations into 3,125% and 8,85%, respectively.Keywords: OFDM,SDR, USRP,Zero Forcing Equalizer